Pathways to success: Exploring the mediating roles of affective learning and intellectual engagement in academic achievement - Bachar Kahil (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: The current study aim to investigate academic self-efficacy with mediating role of affective learning involvement and intellectual engagement on student’s satisfaction and learning performance. Methodology: Using a straightforward sample procedure, 415 participants who answered a self-reported questionnaire were selected to take part in the study. PLS-SEM was used to test the hypotheses. Findings: The result shows that academic self-efficacy has significant and negative impact on affective learning involvement and intellectual engagement. Therefore, moderating impact of academic diligence significantly and positively impact on academic self-efficacy with affective learning involvement and intellectual engagement. Also, mediating impact of affective learning involvement and intellectual engagement significantly and negatively impact among academic self-efficacy and student’s satisfaction and learning performance. Implications/Novel Contribution: According to this study, management in higher education must create effective and efficient rules that incorporate students’ learning performance, academic diligence, and academic self-efficacy. This study is one of the first to examine a paradigm that incorporates academic self-efficacy, affective learning involvement, intellectual engagement, student’s satisfaction and learning performance in a university setting from the standpoint of a developing nation.